EFEKTIVITAS SISTEM INFORMASI DESA DALAM MENINGKATKAN KETERBUKAAN INFORMASI PUBLIK DI DESA LARANGAN - Romadhoni, Muafah Nur; Isnaini Rodiyah (Sawala : Jurnal Administrasi Negara, 2025)
This research aims to describe and analyze the effectiveness of the Village Information System in public information disclosure in Larangan Village. The research uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. Data analysis includes data collection, reduction, presentation, and conclusion drawing. The results of this study show that it is not yet supported by Edy Sutrisno’s theory, namely, program understanding, target accuracy, timeliness, goal achievement, and real change, because there is no clear SOP development related to the implementation of the  Village Information System. In addition, the quality of information on the website is incomplete, including population statistics, but without including other important information, so the community must visit the village government office to obtain information